A short overview of TRANSPORT in 2014 - Junevičius, Raimundas; Prentkovskis, Olegas (Transport, 2014)
"A short overview of TRANSPORT in 2014" Transport, 29(4), pp. 345First Published Online: 16 Dec 2014